Changes in Labour Market Transitions in Ireland over the Great Recession - Adele Bergin; Elish Kelly; Seamus McGuinness (Institute for the Study of Labor (IZA), 2014)
This paper assesses the impact that the 2009 Great Recession had on individual's transitions to and from unemployment in Ireland. The rate of transition from unemployment to employment declined between 2006 and 2011, while the rate from employment to unemployment increased. The impact of some of the factors identified as contributing to the likelihood of a transition taking place were found to have changed over this period. In particular, young people are much less likely to exit unemployment, but at the same time they have a lower risk of becoming unemployed. Education has become an increasingly important factor in both supporting unemployment exits and reducing the risk of becoming unemployed since the recession. The scarring impact of long-term unemployment appears to have fallen substantially in Ireland post-recession. The results from a decomposition analysis show that compositional changes are largely unimportant in explaining the change in the transition rates between 2006 and 2011.
Keywords: J64; J88; 330; labour market transitions; Great Recession; longitudinal data; decomposition techniques; Ireland